The downward continuation of the disturbing potential based on poisson's integral (ESP) - G. Serpas, Juan (Uniciencia, 2004)
This article deals with the test assessment of two different methods for performing the downward continuation of the disturbing potential. The disturbing potential is important in geodesy since it is a fundamental quantity in the determination of the geoid. Nowadays , one of the most used methods for the determination of the disturbing potential is by the processing of airborne gravity data. The resulting disturbing potential is given at flight height, thus the downward continuation from flight height terrain is of great importance. In this study, the downward continuation of the disturbing potential is performed via Poisson´s integral by the use of two methods: the gradient method and the iterative solution. The theoretical aspects of the methods are introduced and developed. Numerical aspects of the computations are treated as well. From the experiment and the used data, we conclude that the iterative solution yields better results, in terms of accuracy, than the gradient method. The test was performed from upward continued disturbing potentials over a mountainous area